Meaning Shift in the Translation of Disney Song Lyrics: A Stylistic Analysis - Yuliarta, Rizqi (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
This research discusess the shift of meaning in the translation of Disney song lyrics from English to Indonesian with a stylistic approach. The three songs analysed are Let It Go, How Far I’ll Go, and Beyond. This study uses a qualitative descriptive method with a comparative analysis technique between the original lyrics and translated version. The results show there are various forms of meaning shifts caused by simplification of language style, removal of symbolic meaning, and changes in sentence structure. Stylistic devices such as metaphor, personification, simile, anaphora and rethorical questions tend to change or disappear in the translated version, which results in a decrease in the expressive power, poetic beauty, and emotional power of the song. While the denotative meaning is retained, the connotative nuanes and depth of meaning in the original lyrics are often not fully conveyed in the translated version. This research shows the importance of maintaining stylistic elements in the translation process to preserve the message and artistic power of song lyrics.